Microfibrillar-associated protein 2 is a prognostic marker that correlates with the immune microenvironment in glioma - Xu, Wanzhen; Geng, Ren; Zhao, Yao; Ma, Xiaoshan; Bai, Yang; Jiang, Yining; Zhao, Liyan; Li, Yunqian (Frontiers in Genetics, 2022)
Aims: Microfibrillar-associated protein 2 (MFAP2), a component of the extracellular matrix, plays key roles in regulating growth factor signal transduction and various malignant tumors. However, the clinicopathological features of MFAP2 in gliomas have not been elucidated to date. Methods: TCGA and CGGA databases were used to study the expression of MFAP2 in glioma and its relationship with clinicopathological features of patients with glioma. Western blotting was performed to detect the expression of MFAP2 protein in tissue samples from glioma patients. Gene set enrichment analysis (GSEA) was applied to detect biological processes and signal pathways related to MFAP2. Single-sample GSEA, TIMER 2.0, and TISIDB databases were used to evaluate the role of MFAP2 in tumor immune characteristics. The prognostic role of MFAP2 in glioma was analyzed using the Kaplan–Meier method and Cox regression. Survival data were used to establish a nomogram prediction model. Results: MFAP2 expression was significantly elevated in gliomas. ROC analysis revealed good discrimination of MFAP2 between glioma and normal tissues. High expression of MFAP2 was associated with malignant phenotypes, such as histological type. Based on GSEA, we identified pathways associated with high MFAP2 expression. High MFAP2 expression was related to the infiltration of tumor immune cells, including Th2 cells and macrophages, and correlated with key markers of T-cell exhaustion. Based on the TISIDB database, MFAP2 was observed to be associated with chemokines, chemokine receptors, and multiple immunoinhibitors in glioma. Kaplan–Meier survival analyses revealed that high MFAP2 expression predicted poor OS, DSS, and PFS in patients with glioma. By combining MFAP2 and other prognostic factors, a nomogram prognostic prediction model was constructed, which demonstrated an ideal prediction effect. Conclusions: MFAP2 is a potential prognostic marker that plays a key role in glioma development given its association with malignant phenotypes, cancer-related pathways and tumor immunity.